THE TREATED EGGSHELLS AS A NEW BIOSORBENT FOR ELIMINATION OF CARBARYL PESTICIDE FROM AQUEOUS SOLUTIONS: KINETICS, THERMODYNAMICS AND ISOTHERMS - ABDELHAMID BAKKA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2016)
The efficiency of treated eggshells (TES) for removing the carbaryl pesticide from aqueous solutions was examined by biosorption process. Batch mode experiments were conducted using various parameters such as contact time, temperature, biosorbent amount, carbaryl concentration and pH. Removal efficiency of carbaryl by the TES attained 87.35 % after 60 min of contact time, using 10 mg·L-1 of pesticide and 1.5 g·L-1 of biosorbent. The results indicate that Freundlich equation is well described with the carbaryl adsorption, with correlation coefficient R2 value of 0.99. They showed that the biosorption processes were spontaneous and exothermic. The Gibbs energy ∆G increased with increase in temperature indicating an increase in feasibility of biosorption at low temperature. These results show that treated eggshells can be employed as an alternative to commercial adsorbents in the removal of pesticides from aqueous solutions.